META-ANALYSIS OF MORTALITY AND COMPLICATION RATES IN LAPAROSCOPIC VS. OPEN LIVER RESECTION - Rama MHD Ghaleb almasri; Shaikh Salman Khaled AlKhalifa; Dr. Mohd shahrukh; Mohamad bilal TAKRITI; Jumana Jamal abuthan; Ahmad Ghassan Ghatasheh; Rahaf ghazal; Dr Pushpendra Kumar Nain; Maitha Rashed Alawadi; Ibrahim Almasri (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Hepatobiliary diseases such as hepatocellular carcinoma, metastatic liver tumours, and hepatic benign lesions are treated with liver resection which remains an important technique. Traditional open liver resection (OLR) is the standard procedure, but laparoscopic liver resection (LLR) is being more widely accepted. This meta-analysis aims to evaluate whether LLR is associated with lower mortality and complication rates as compared to OLR. Meta-analysis PRISMA, randomised controlled trials (RCTs), cohorts, and retrospective studies employing LLR vs OLR were reviewed. Important outputs that were gauged included rates of mortality, rates of overall complications, length of hospitalisation, and post-operative complications. Subgroup classification based on tumour sizes, grades of liver functions, and levels of resection were used to understand outcomes. Bias was evaluated using funnel plot analysis and Egger's test. The pooled mortality rate for LLR was significantly lower (1.9%) versus OLR (3.7%). The most notable improvement was for patients with minor resections and benign liver diseases. Likewise, overall complication rates were lower in LLR (14.5% vs 21.8%), significantly reduced cases of postoperative bleeding, bile leakage, infectious complications, and pulmonary complications. LLR patients had shorter hospital stays (6.1 vs 9.4 days) and a lower re-admissions rate (4.3% vs 6.7%), which positively impacted their postoperative recovery. In patients with well-preserved liver function and tumours of up to 5 cm in size, LLR has a specific advantage. In contrast, for higher volume centres, the majority of resections and cirrhosis patients, the results were similar. These sensitivity analyses and Egger's test further corroborate this finding that publication bias was not exposed. This meta-analysis suggests that LLR is a viable option compared to OLR and demonstrates lower complication rates, better recovery, and lower mortality. However, the challenges of the technique, patient selection, complexity of the procedure, and increased operation time remain. Further well-conducted and more RCTs should focus on improving patient selection and evaluating effective prolonged oncology outcomes. In turn, widening the approaches to controlled rehabilitation in robotic technologies and providing basic instructions will improve the results of laparoscopic surgery of the liver.